Effect of Cu2Te Back Surface Interfacial Layer on Cadmium Telluride Thin Film Solar Cell Performance from Numerical Analysis - Harif M.N.; Doroody C.; Nadzri A.; Nisham Rosly H.; Ahmad N.I.; Isah M.; Amin N. (MDPI, 2024)
Even though substantial advances made in the device configuration of the frontal layers of the superstrate cadmium telluride (CdTe) solar cell device have contributed to conversion efficiency, unresolved challenges remain in regard to controlling the self-compensation and minority carrier recombination at the back contact that limits the efficiency. In this study, a SCAPS-1D simulator was used to analyze the loss mechanism and performance limitations due to the band-bending effect upon copper chloride treatment and subsequent Cu2Te layer formation as the back contact buffer layer. The optimal energy bandgap range for the proposed back surface layer of Cu2Te is derived to be in the range of 1.1 eV to 1.3 eV for the maximum conversion efficiency, i.e., around 21.3%. Moreover, the impacts of absorber layers carrier concentration with respect to CdTe film thickness, bandgap, and operational temperature are analyzed. The optimized design reveals that the acceptor concentration contributes significantly to the performance of the CdTe devices, including spectral response. Consequently, the optimized thickness of the CdTe absorber layer with a Cu-based back contact is found to be 2.5 m. Moreover, the effect of temperature ranging from 30 C to 100 C as the operating condition of the CdTe thin-film solar cells is addressed, which demonstrates an increasing recombination tread once the device temperature exceeds 60 C, thus affecting the stability of the solar cells. 2023 by the authors.